Feint praise. (Economist, 2017)
The article discusses the Russian President Vladimir Putin's response to U.S. President Barack Obama's issuing of sanctions against Russia for its alleged role trying to influence the 2016 presidential election through computer hacking. U.S. President-elect Donald Trump's perspective on Putin's response to U.S. sanctions is discussed.